Musthalah al-Tanash Nasyatuhu wa Ta’shiluhu wa Huduruhu fi al-Adab al-‘Arabi - al-Ansi, Abd al-Salam Humud Ghalib (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2024)
A number of contemporary Arab critics have sought to root many Western critical concepts by searching for their origins in the ancient Arab and rhetorical heritage, including, for example, “intertextuality.” These critics agree that the ancient Arab critical heritage is full of critical theories and concepts, and it is necessary to return to it to uncover the origins of these modern Western theories and concepts, and to reintegrate them into modern criticism. The concept of intertextuality is one of the most Western concepts exposed to rooting in contemporary Arab criticism. This concept was rooted by linking it to old concepts created by Arab critics in the past, such as quotation, inclusion, literary theft, and others. Thus, Arab critics have enriched the human critical heritage with critical theories that they produced and applied to Arab poetic creativity. Arabs knew the idea of intertextuality in its concept, dimensions, and some of its functions, but they did not naturally create this Western term. Some modern Arab critics sought to purify the concept of intertextuality from its impurities that make it a dangerous concept, so that it could be rooted and considered a new and contemporary formulation of the concept of legalized thefts, which Abdul Qaher Al-Jurjani defined as